A metabolite of daidzein, 6, 7, 4′‐trihydroxyisoflavone, suppresses adipogenesis in 3T3‐L1 preadipocytes via ATP‐competitive inhibition of PI3K. Issue 8 (4th June 2013) - Seo, Sang Gwon; Yang, Hee; Shin, Seung Ho; Min, Soyun; Kim, Yeong A.; Yu, Jae Gak; Lee, Dong Eun; Chung, Min‐Yu; Heo, Yong‐Seok; Kwon, Jung Yeon; Yue, Shuhua; Kim, Kee Hong; et al.
<x xml:space="preserve">Abstract</x> Scope Daidzein is one of the major soy isoflavones. Following ingestion, daidzein is readily metabolized in the liver and converted into hydroxylated metabolites. One such metabolite is 6, 7, 4′‐trihydroxyisoflavone (6, 7, 4′‐THIF), which has been the focus of recent studies due to its various health benefits, however, its anti‐adipogenic activity has not been investigated. Our objective was to determine the effects of 6, 7, 4′‐THIF on adipogenesis in 3T3‐L1 preadipocytes and elucidate the mechanisms of action involved. Methods and results Adipogenesis was stimulated in 3T3‐L1 preadipocytes. Both 6, 7, 4′‐THIF and daidzein were treated in the presence and absence of mixture of isobutylmethylxanthine, dexamethasone, and insulin (MDI). We observed that 6, 7, 4′‐THIF, but not daidzein, inhibited MDI‐induced adipogenesis significantly at 40 and 80 μM, associated with decreased peroxisome proliferator‐activated receptor‐γ and C/EBP‐α protein expression. 6, 7, 4′‐THIF significantly suppressed MDI‐induced lipid accumulation in the early stage of adipogenesis, attributable to a suppression of cell proliferation and the induction of cell cycle arrest. We also determined that 6, 7, 4′‐THIF, but not daidzein, attenuated phosphatidylinositol 3‐kinase (PI3K)/Akt signaling pathway. 6, 7, 4′‐THIF was found to inhibit PI3K activity via direct binding in an ATP‐competitive manner. Conclusion Our results suggest that 6, 7, 4′‐THIF suppresses adipogenesis in 3T3‐L1 preadipocytes by directly targeting PI3K. Soy isoflavones like 6, 7, 4′‐THIF may have potential for development into novel treatment strategies for chronic obesity.